Hubungan Pengetahuan Tentang ASI Eksklusif dengan Perilaku dalam Pemberian ASI Eksklusif pada Ibu di Wilayah Kerja Puskesmas Tegalrejo Kabupaten Magelang Tahun 2013 - Yustina Ananti; Gunarmi Gunarmi; Prestawatiningsih Prestawatiningsih (LPPM STIKES Guna Bangsa, 2015)
Background : Breastfeeding (ASI) is the most suitable food for infants as well as having the highest scores compared to baby food made of human or animal milk such as cow's milk, and others. Maternal knowledge is not only influenced by the educational level of the mother but also the mother obtained resources from the external environment, especially the role of mass media in providing information. Information presented mass media affect the information that is exclusive breastfeeding or formula milk advertisements currently being intensively carried out by the milk producers. Objective : Knowing the relationship between knowledge about the behavior of exclusive breastfeeding with exclusive breastfeeding in mothers. Method : This study is an observational study with this type, using a cross-sectional design. The number of samples in this study were 58 respondents. Results : Most respondents had sufficient knowledge and most of the respondents did not breastfeed exclusively . There is a relationship between knowledge about the behavior of exclusive breastfeeding with exclusive breastfeeding in mothers in the Work Area Health Center Tegalrejo Tegalrejo District of Magelang regency with p value of 0.000. Conclusions : There is a relationship between knowledge about exclusive breastfeeding with exclusive breastfeeding behavior.